2018
DOI: 10.1016/j.jconrel.2018.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor efficacy of hyaluronan-based nanoparticles for the co-delivery of drugs in lung cancer

Abstract: Combinations of therapeutic agents could synergistically enhance the response of lung cancer cells. Co-delivery systems capable of transporting chemotherapeutics with different physicochemical properties and with the simultaneous release of drugs remain elusive. Here, we assess the ability of nanoparticles of 30-nm diameter obtained from the self-assembly of hyaluronan-based copolymer targeting CD44 receptors to encapsulate both gefitinib and vorinostat for effective combinational lung cancer treatment. Drug l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(36 citation statements)
references
References 47 publications
1
33
2
Order By: Relevance
“…3c , the SPR signal of larger HA-particles (150 nm) was significantly higher than that of those of smaller diameters (30 nm). These observations are consistent with recent in vitro experiments performed on different lung cancer cell lines expressing different level of CD44 71 . Richter’s lab also recently observed the multivalent interaction between CD44 and high molecular weight HA by a multivalent interaction model 72 .…”
Section: Resultssupporting
confidence: 93%
“…3c , the SPR signal of larger HA-particles (150 nm) was significantly higher than that of those of smaller diameters (30 nm). These observations are consistent with recent in vitro experiments performed on different lung cancer cell lines expressing different level of CD44 71 . Richter’s lab also recently observed the multivalent interaction between CD44 and high molecular weight HA by a multivalent interaction model 72 .…”
Section: Resultssupporting
confidence: 93%
“…29,30 For instance, Jeannot et al reported HA-b-poly(γ-benzyl-L-glutamate) nanoparticles that could actively target to the CD44 receptor for delivery of vorinostat and gefitinib with strong tumor growth inhibition. 31 In another example, Gu et al synthesized HA-b-poly(trimethylene carbonate-co-dithiolane trimethylene carbonate) that was capable of high drug loading and tumor-targeted delivery of bortezomib to myeloma in vivo. The HA-based nanoparticles exhibited a broad therapeutic window and enhanced tolerance with more effective growth suppression of CD44-overexpressed tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular uptake of NLC-verteporfin involved endocytosis processes, taking more time than free verteporfin, part of which can rapidly diffuse across cell membranes. NLC-verteporfin uptake was also shown in tumor spheroids, which mimic in vivo tumors with tumor cell interactions and gradients of nutrients and oxygen [22,23,24,25]. The slower kinetic of NLC-verteporfin uptake compared to free verteporfin did not impair the efficiency of verteporfin phototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which the OVCAR3 cells resisted to PDT in 2D culture but not in spheroids is still unknown. These results highlighted that the toxicity of drugs significantly varied depending on whether it is assessed in spheroids or in monolayer cell cultures, and this thus underlined the importance of using spheroids before moving forward in vivo experiments in mice [22,23,25]. Further experiments are needed to study NLC-verteporfin uptake and cytotoxicity in multicellular spheroids, which will reproduce both tumor cells and microenvironment [24].…”
Section: Discussionmentioning
confidence: 99%